(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores the ecological and environmental impact of termites on the biosphere, examining their roles in nutrient cycling, soil formation, and carbon storage. The analysis considers both the beneficial and harmful effects of termites in various ecosystems, detailing how their interactions influence biodiversity, plant growth, and atmospheric chemistry. Through a literature review, empirical observations, and a critical discussion, this paper aims to provide insights into termites’ roles in maintaining ecosystem stability and implications for climate change.